Influence of growth rate on the physiological response of marine Synechococcus to phosphate limitation - Kretz, Cécilia B.; Bell, Doug W.; Lomas, Debra A.; Lomas, Michael W.; Martiny, Adam C. (Frontiers in Microbiology, 2015)
Phosphate (P) is an important nutrient potentially limiting for primary productivity, yet, we currently know little about the relationship between growth rate and physiological response to P limitation in abundant marine Cyanobacteria. Thus, the aim of this research was to determine how variation in growth rate affected the physiology of marine Synechococcus WH8102 and CC9311 when growing under high N:P conditions. Experiments were carried out in chemostats with a media input N:P of 441 and we estimated the half saturation concentration for growth under P limiting conditions (Ks,p) and cellular C:N:P ratios. The Ks,P values were the lowest measured for any phytoplankton and on par with ambient P concentrations in oligotrophic regions. We also observed that both strains were able draw down P below 4nM. Both Ks,p and drawdown concentration were lower for the open ocean vs. coastal Synechococcus strain, which may be linked to differences in P acquisition genes in these strains. Cellular C:P and N:P ratios were significantly higher in relation to the Redfield ratio for both Synechococcus strains but we saw no difference in these ratios among growth rates or strains. These results demonstrate that Synechococcus can proliferate under very low P conditions and also that genetically different strains have unique physiological responses to P limitation.